Implementation research on common cancers (lung, breast, and colorectal) in Asia – a systematic review - Panigrahi, Ansuman; Mohanty, Swati Sambita; Behera, Purnashashi; Dandsena, Rutuparna Sibani; Sahu, Priyanka; Pati, Sanghamitra (Frontiers in Oncology, 2025)
IntroductionImplementation research is crucial for implementing evidence-based interventions in real-world settings. This study aims to assess and collate existing evidence on implementation research related to common cancers (lung, breast, and colorectal) conducted in Asia.MethodsA comprehensive literature search was conducted using databases, including PubMed, Embase, ScienceDirect, EBSCO, Web of Science, and Scopus, covering publications from 2004 to 2024. Additionally, free search engines and repositories, such as Google Scholar and Shodhganga, were searched to identify other relevant unpublished studies. A systematic review, adhering to the PRISMA 2020 guidelines, was conducted. From 5750 articles, 11 studies were included that specifically investigated implementation strategies for cancer interventions in Asian populations.FindingsThe review included eleven studies; four implementation studies on lung and breast cancers, and three on colorectal cancers. The included studies explored various interventions to improve cancer care, including training, awareness, and access as key implementation barriers. Context-specific strategies were crucial for successful adoption and sustainability. Most studies evaluated reach, acceptability, feasibility, adoption, fidelity, implementation cost, appropriateness, and sustainability, offering valuable insights into implementation research.InterpretationImplementation research on common cancers (lung, breast, colorectal) in Asia is very limited, underscoring the necessity of tailored implementation strategies to integrate cancer care interventions in Asia effectively.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier PROSPERO CRD42024542247.